ECOLOGICAL CHARACTERISTICS OF THE DIFFERENT ECOSYSTEMS in COASTAL areas OF THE ANDAMAN ISLANDS - Dilipan, E.; Nobi, E.P.; Thangaradjou, T. (Journal of Experimental Sciences)
Coastal ecosystems are well known for their higher primary and secondary productivity and support of diverse floral and faunal communities. Especially coral reef and seagrasses create, as well as occupy, important niches in shallow water environments. Physico- chemical characteristics of the critical habitats (Mangrove, seagrass, dead coral bed and sandy beach) of Andaman islands were studied. Physico-chemical parameters recorded in 18 stations showed distinct variations among different ecosystems, especially chemical parameters showed notable variations in all these ecosystems. Sediment characters showed significant variations: pH of the sediments varied between 8.1 and 8.6 in all the sampling locations and the electrical conductivity of the sediments varied between 2.1 and 4.1dSm-1. Sediment nutrients varied widely: nitrogen (22-52 kg/acre), phosphorus (10-15 kg/acre) and potassium (55-73 kg/acre). Though the physico-chemical parameters showed distinct variations among different ecosystems, they are within the optimum range reported for the specific ecosystems prevailing in the area. In general, the nutrient level of water in the seagrass and mangroves was low when compared similar ecosystems of the mainland. It is important to note that, though the ambient water quality of these ecosystems is at the optimum level reported for the respective ecosystems, proper attention should be paid to maintain the subtle nature of the ecosystems of the islands, under the post-tsunamic geomorphological variations, increasing national and international tourism activity and the changing climatic conditions.